Improving Student’s Skills in Reading the Al-Quran Through the Tahsin Program at the Islamic Boarding School - Putri, Muryani; Indria, Anita; Pasaleron, Roni (Ahlussunnah: Journal of Islamic Education, 2022)
This research aims to determine the forms of activities and forms of guidance for class VII students at the Madrasah Tsanawiyah Islamic Boarding School Prof. Dr. Hamka Maninjau. This type of research takes the form of field research using a qualitative descriptive approach, namely research that tries to describe and interpret a situation that is currently occurring in the field. Data collection uses observation, interviews, and documentation. The data sources in this research were the principal of Madrasah Tsanawiyah, tahsin teachers, and class VII students of Madrasah Tsanawiyah Islamic Boarding School, Prof. Dr. Hamka Maninjau. Data were analyzed by triangulation through 3 stages, namely preparation, checking, and evaluation. The conclusion of this research is; i) preparation of teachers and students, namely teaching materials, making syllabi, lesson implementation plans, making concept maps, collecting resources, stationery and tahsin teaching materials needed for teaching such as the Al-Qur'an and memorizing books, ii) equipment prepared is that the teacher makes a syllabus and prepares a learning implementation plan, iii) the media used is that the teacher uses books, whiteboards, and markers during tahsin activities. Meanwhile, the sources used are the Al-Qur'an, memorized books, and the Iqra' book volume iv) the obstacle faced is the lack of time in tahsin activities, v) the type of assessment is oral and written tests. In tahsin guidance there is guidance with halaqqah: i) the approach used by the teacher is the talaqi method, ii) guidance is not always in accordance with the plan that has been made, there are students who already understand and there are also those who do not fully understand the tahsin material, iii) Obstacles that arise found in students' verbal assessments, namely being sleepy and not repeating lessons, iv) students' responses to tahsin guidance can improve how to memorize the Al-Qur'an according to tajwid rules.